INTEGRASI SIG DENGAN USLE DALAM PENILAIAN EROSI DI DAS WAIRUTUNG - Mohammad Lasaiba; Ferdinand S. Leuwol; Wiclift S. Pinoa; Irvan Lasaiba; Roberth B. Riry; Syawal Sandia (Jurnal Tanah dan Sumberdaya Lahan, 2023)
This study aimed to assess the erosion hazard level in the Wairutung Watershed. The land unit in this study was generated from the overlaying land use maps, slope maps, and soil types maps.  The class of vulnerability was determined based on the sum of the parameters' rating results using a computer-based Geographic Information System (GIS) with the ArcGIS program, which was integrated with the Universal Soil Loss Equation (USLE) model. The results indicated the division of 4 classes of landslide hazards consisting of a very light class with an area of ​​2,900.865 ha spread over land units with alluvial soil types. The medium type, with a total area of ​​3,683.285 ha, is spread over land units with podzolic soil types. Heavy type with a total area of ​​1,458.367 ha and the whole area is spread over land units with podzolic and Litosol soil types. The erosion hazard level is very heavy, with a total area of ​​421.97 ha and is spread over land units with Podzolic and Litosol soil types.